(untitled) (Islas, 2024)
Introduction: A methodology for photography as a research object points out, in a precise and objective manner, the fundamental visual, aesthetic, communicative and operative problems presented by its teaching in non-systemic training processes. Resorting to languages and forms of (re)presentation, which derive towards other fields or manifestations of artistic creation, such as those presented in this article, allow us to characterize the formal and conceptual state of photography as a didactic and investigative process. Methods: Considerations and procedures that allowed the assumption of different research methodologies based on the Visual Arts, such as independent photography, the photographic series, the photographic essay, the photodiscourse and the visual quotation, are presented. Results: Some considerations that facilitate the understanding of the essentiality of these terms from the grammar of a new «way of seeing», according to Jean-Claude Lemagny’s aesthetic clock or circle of images, are identified and analyzed. Conclusions: Photography as a research object proposes to use photography as a tool to investigate and explore different aspects of society, culture and the artistic-social environment. Research based on the Visual Arts uses the methodology of qualitative research, where we work with various techniques and visual tools such as photography. This methodology involves observing, analyzing and documenting visual images to understand and reflect on different didactic-research aspects, but also within the expressive-communicative environment of the image. Jean-Claude Lemagny’s aesthetic clock or circle of images allows to analyze and understand the process of production and reception of photographic images.